PENGARUH KINERJA LINGKUNGAN PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Dewi, Ni Putu Diana Permata; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022DO - 10.24843/EEB.2022.v11.i10.p03, 2022)
The purpose of this study was to determine the effect of environmental performance on socially responsible companies (study of mining companies listed on the Indonesia Stock Exchange for the period 2018-2020). Legitimacy theory and Stakeholder theory are used as theoretical foundations to support the research model. The research was conducted on mining companies listed on the IDX for the 2018-2020 period. The total population is 40 companies. The sample in this study was 14 with purposive sampling technique for 3 years of observation, so as to obtain 42 observations. The data analysis technique used simple linear regression analysis. Based on the results of data analysis obtained that environmental performance has a positive effect on Corporate Social Responsibility in Mining Companies Listed on the IDX for the 2018-2020 period. The higher the performance of mining companies, the higher the Corporate Social Responsibility carried out.